Development of Student Worksheet on Rectangular Based on Yogyakarta Culture for Grade VII of Junior High School Students - Kintoko Kintoko; Wahyu Nurrohman (Universitas Tidar, 2020)
This research aims to develop and quality teaching materials for mathematics student worksheets based on Yogyakarta culture in rectangular materials for grade VII of junior high school students that can be valid, practical, and effective. This research is a development that refers to 3D development models, namely: define, design, and develop. The result shows that (1) there are the development of teaching materials for math worksheets (LKS) based on Yogyakarta culture on rectangular material fulfills the criteria of validity, practicality, and effectiveness; (2) based on the validity aspect of the math worksheets teaching materials, valid criteria were obtained which were reviewed from the material experts' assessment and it was obtained that the value is 3.1 and the results of the material experts' assessment by mathematics lectures and teachers obtained valid criteria with an average of 3.00; (3) based on the practical aspect of math worksheets teaching materials, students' responses were very practical with an average value 3.27; (4) based on the aspect of effectiveness by comparing the average value of students work and the Minimum Mastery Criteria (KKM) set by the school, the result of student value was more than the KKM. After using mathematics LKS teaching materials, 100% scored above the Minimum Mastery Criteria with an average of 88.57. The teaching materials for math worksheets based on Yogyakarta culture meet the criteria of validity, practicality, and effectiveness to improve the learning achievement of grade VII at SMP IT Masjid Syuhada.